Overview of Self Adjustment Students Based On Personality Types - Shofia, Atikah Rahma; Syukur , Yarmis (The Future of Education Journal, 2024)
The research is motivated by the phenomenon of many students struggling to adapt to the school environment. Self-adjustment is crucial for students, particularly in the 10th grade. Personality is one of the factors that influences self-adjustment. The research sample consisted of 187 X grade students from SMAN 1 Kubung, selected using the Simple Random Sampling technique. The research instruments included self-adjustment questionnaires and personality type questionnaires. The data were analyzed using descriptive statistical techniques and the t-test. The research results show: (1) the self-adjustment level of X grade students at SMAN 1 Kubung is in the high category, (2) the self-adjustment level of students with an introverted personality type is in the high category, (3) the self-adjustment level of students with an extroverted personality type is in the high category, and (4) Ha is rejected, there is no significant difference between the adjustment of students with the Introvert and Extrovert personality types at SMAN 1 Kubung. In an effort to help alleviate student adjustment problems,  guidance and counseling services that can be provided include orientation services, informational services, and group counseling services.